Studi Etnomedisin Tumbuhan Obat Sebagai Antidiabetes dan Antikanker di Kabanjahe Sumatra Utara Indonesia - Dinda Rizka Manurung; Nur Aira Juwita; Wawan Sujarwo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to explore and document the use of medicinal plants by the community in Kabanjahe Subdistrict, Karo Regency, which are traditionally used to treat diabetes and cancer. Furthermore, the study assesses the relative importance of each plant based on its frequency of use and the level of agreement among informants. A descriptive qualitative method with an ethnomedicine approach was employed. Data were collected through semi-structured interviews with informants selected using purposive and snowball sampling techniques. The data were analyzed descriptively and presented in tables accompanied by narrative explanations. The usefulness of each plant species was evaluated using three ethnobotanical indices: Use Value Index (UVI), Relative Frequency of Citation (RFC), and Informant Consensus Factor (ICS). The results indicate the use of 107 plant species from 47 families as traditional medicine. The most commonly used families for diabetes treatment include Zingiberaceae, Lamiaceae, Asteraceae, and Rutaceae. The most frequently utilized plant parts are leaves, stems, and rhizomes. Preparation methods include boiling, grinding, and squeezing, with oral consumption being the most common mode of administration. UVI values ranged from 1 to 2.5. RFC values for antidiabetic plants ranged from 0.009 to 0.057, while anticancer plants ranged from 0.009 to 0.048. ICS values ranged from 6 to 20 (antidiabetic) and from 6 to 32 (anticancer). In conclusion, the people of Kabanjahe still rely heavily on local medicinal plants for traditional treatment. These findings reflect the strong potential for developing phytopharmaceutical products rooted in local wisdom, while also supporting the preservation of biodiversity and traditional knowledge of the Karo community. Keywords: Anticancer, Antidiabetes, Ethnomedicine, Karo Regency, Medicinal Plants